Principles and practice of sport management - Hums, Mary A. PhD; Masteralexis, Lisa Pike JD (Burlington, MA Jones & Bartlett Learning, 2024)
"Principles and Practice of Sport Management provides students with the foundation they need to prepare for a variety of sport management careers. Intended for use in introductory sport management courses at the undergraduate level, the focus of this text is to provide an overview of the sport industry and cover basic fundamental knowledge and skill sets of the sport manager, as well as to provide information on sport industry segments for potential employment and career opportunities"--
Part I: foundations of sport management -- History of sport management -- Management principles applied to sport management -- Marketing principles applied to sport management -- Finance and economic principles applied to sport management -- Legal principles applied to sport management -- Ethics applied to sport management -- Part II: amateur sport industry -- High school and youth sport -- Collegiate sport -- International sport -- Part III: professional sport industry -- Professional sport -- Sports agency -- Part IV: sport industry support segments -- eSports -- Facility management -- Event management -- Sport sales -- Sport sponsorship -- Sport analytics -- Sport communications -- The sporting goods and licensed products industries -- Part V: lifestyle sports -- Recreation and golf club management -- Part VI: career preparation -- Strategies for career success
Includes accompanying online ancillary resource
Includes bibliographical references and index